Visca el Barça Visca Catalunya! Konteksty tożsamościowe i regionalne w wypowiedziach medialnych katalońskich piłkarzy klubu FC Barcelona - Stępień, Patryk (Studia Edukacyjne, 2023)
Football is one of the best known global cultural practices, making it a research field for social scien- tists, including educators. FC Barcelona is one of the greatest clubs around the world, with numerous fans. The footballers of FC Barcelona are very popular, too, and many supporters follow them on social media. It means that footballers can become a kind of authorities for the fans, and their statements may be considered as an inspiration or model to find and explore self-identity, the value of the region in their lives, etc. The paper analyzes media interviews with the Catalan footballers of FC Barcelona and the identity and regional contexts found there. The results can be used as an introduction to research about the role of a footballer’s authority in a fan’s life and as reference materials for teachers in regional education and interculturalism.